2019
DOI: 10.1016/j.tranon.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PP2A and Its Endogenous Inhibitors in Neuroblastoma Cell Survival and Tumor Growth

Abstract: High-risk neuroblastoma continues to carry a poor prognosis. Nearly 50% of these tumors relapse following extensive treatment regimens. Protein phosphatase 2A (PP2A), a tumor suppressor, has been shown to be downregulated in many human cancers via multiple mechanisms including upregulation of its endogenous inhibitors, I2PP2A or CIP2A. We hypothesized that inhibition of the endogenous PP2A inhibitors or activation of PP2A would decrease tumorigenicity in human neuroblastoma cells. Four human neuroblastoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…The present results indicated JS-K stimulated a signi cant enhancement of PP2A activity. Several studies indicate that PP2A can dephosphorylate and inactivate both MEK and ERK proteins while PP2A inhibitors OA can induce MEK and ERK1/2 phosphorylation [4,5,22]. The present results demonstrated that PP2A suppression could antagonize the inhibition effect of JS-K on the ERK signaling pathway including dephosphorylation of MEK, ERK, Elk-1, c-Myc, and c-Fos.…”
Section: Discussionsupporting
confidence: 53%
“…The present results indicated JS-K stimulated a signi cant enhancement of PP2A activity. Several studies indicate that PP2A can dephosphorylate and inactivate both MEK and ERK proteins while PP2A inhibitors OA can induce MEK and ERK1/2 phosphorylation [4,5,22]. The present results demonstrated that PP2A suppression could antagonize the inhibition effect of JS-K on the ERK signaling pathway including dephosphorylation of MEK, ERK, Elk-1, c-Myc, and c-Fos.…”
Section: Discussionsupporting
confidence: 53%
“…The present results indicated JS-K stimulated a signi cant enhancement of PP2A activity. Several studies indicate that PP2A can dephosphorylate and inactivate both MEK and ERK proteins while PP2A inhibitors OA can induce MEK and ERK1/2 phosphorylation [23][24][25]. The present results demonstrated that PP2A suppression could antagonize the inhibition effect of JS-K on the ERK signaling pathway including dephosphorylation of MEK, ERK, Elk-1, c-Myc, and c-Fos.…”
Section: Discussionsupporting
confidence: 53%
“…A cluster analysis heatmap ( Figure 3C ) was employed to visually depict the top 100 differentially expressed genes, facilitating a more comprehensive understanding of the distinctions between HG-NB and LG-NB groups, thereby highlighting their significant differences. Based on the transcriptome results and relevant literature on NB ( 22 27 ), we selected 6 reported differentially expressed genes, namely MGST1 , SERPINE1 , IGF2 , CIP2A , CHL1 , and ERBB3 for RT-PCR validation. Our RT-PCR results demonstrated that the relative expressions of MGST1 , SERPINE1 , IGF2 , and CIP2A were significantly increased in HG-NB compared to LG-NB, while the relative expressions of CHL1 and ERBB3 were significantly decreased in HG-NB compared to LG-NB.…”
Section: Resultsmentioning
confidence: 99%